Effect of Organic Decayed Material (or Bokashi Fertilizer ) and Varietas on the Grwoth and Yield of Sweet Corn ( Zea mays saccharata Sturt). - Robaniah Robaniah (Universitas 17 Agustus 1945 Samarinda, 2019)
The aims of research were to determine the effect Bokashi fertilizers and varietas as well as their interaction on the growth and yield of sweet corn, and to determine the proper dosage of Bokashi fertilizer to produce maximum production on certain varieties.The research was conducted starting from March 2016 to July 2016, from land preparation up to the last data collection. It was carried out at Jl. Pendidikan, North Sangatta sub district, East Kutai District. The research using Random Block Design (RBD), with 2 factorial and 3 replications. The first factor was Bokashi Fertilizers (B), consisting of four levels, namaly : no Bokashi application or control (b0), 10 tons/ha equal to 3,5 kg/plot (b1), 15 tons/ha equal to 5,25 kg/plot (b2), and 20 ton/ha equal to 7 kg/plot (b3). The second factor was the maize varieties (V), consisting of there varieties, namaly : Bonanza F1 (v1), Sweet Boy (v2), and Sweet Corn (v3).Results of the research showed that the Bokashi fertilizer treatment has no significant effect on the age of male flowers and female flowers emerge. But it had significant effect on the production of cobs per hectare. And it had very significant effect on the plant height at ages 15 days, 30 days and 45 days affer planting, cob lenght and cob diameter. The highest cobs production was attained at the b1 treatment with 7,68 tonnes/ha, while the lowest one was attained at the b0 treatment with only 7,48 tonnes/ha.Treatment of varieties did not affect significanttly on the plant height at ages of 15 days, 30 days and 45 days after planting, age of male flowers and female flowers emerge, cob length, cob diameter and production of cobs per hectare.Interaction treatment had no significand effect on the plant height at ages of 15 days, 30 days and 45 days after planting, age of male flowers and female flowers emerge, cob lenght, cob diameter and production of cobs per hectare.